Rational environmental management as a guideline for the economic transformation of production relations - Pizhurin Andrey; Goncharova Oksana; Sazhneva Lioubov; Salazar Cristian (BIO Web of Conferences)
The article considers the conceptual foundations of rational nature management as a key reference point for the economic transformation of production relations. In the conditions of the modern world economy, characterised by the growing environmental crisis and limited natural resources, rational nature management is the most important factor of sustainable development. The authors analyze historical aspects of the evolution of production relations and identify the main stages of integration of environmental criteria into economic models. The aim of the study is to identify optimal mechanisms and tools that promote the harmonization of economic activity with environmental requirements. The study considers approaches to the formation of environmentally-oriented production processes and natural resource management at the level of enterprises and the national economy as a whole. It also analyses examples of successful integration of environmental principles into production practices in various countries and regions. Special attention is paid to the analysis of legislative and regulatory frameworks that ensure the implementation of the principles of rational nature management in the economy. The article offers recommendations for improving government policy and corporate strategies in the field of ecology; it also discusses the prospects for further development of environmentally oriented production models.